2014
DOI: 10.1159/000365205
|View full text |Cite
|
Sign up to set email alerts
|

Facial Angioedema and Stroke

Abstract: Background: Angioedema (AE) in stroke has been reported exclusively after thrombolysis with recombinant tissue-type plasminogen activator (rtPA). Previous studies proposed the insular cortex to play a specific role in the development of AE after stroke. We evaluated the incidence of AE in acute stroke and tried to identify the predominantly involved brain structures. Methods: We performed a retrospective search of our stroke database for patients with an AE. MRI data were analyzed by adapting the images to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 16 publications
1
30
2
Order By: Relevance
“…Higher frequency of insular involvement in OA patients was found by Hill et al [2], however, a nonblinded assessment of imaging was performed by the treating physician, which could have introduced a potential imaging assessment bias. The high frequency of insular cortex ischemia in OA patients (80%) found by Werner et al, was evaluated by MRI in 15 patients with OA, however, patients without OA were not analyzed [5]. Although we are not able to definitely exclude a possible contribution of insular ischemia for development of alteplase-related OA, our study does not support the suggestion that insular ischemia plays a key role in its pathophysiology.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Higher frequency of insular involvement in OA patients was found by Hill et al [2], however, a nonblinded assessment of imaging was performed by the treating physician, which could have introduced a potential imaging assessment bias. The high frequency of insular cortex ischemia in OA patients (80%) found by Werner et al, was evaluated by MRI in 15 patients with OA, however, patients without OA were not analyzed [5]. Although we are not able to definitely exclude a possible contribution of insular ischemia for development of alteplase-related OA, our study does not support the suggestion that insular ischemia plays a key role in its pathophysiology.…”
Section: Discussioncontrasting
confidence: 69%
“…Other case control-studies found a higher frequency of OA in women [3,5] and, in our study, female sex was an independent risk factor for OA, which is in accordance to a large cohort study of medication-related angioedema incidence [9]. The reason for this sex difference is not clear, but may include the influence of sex hormones on the regulation of inflammation and an increased T h 2 immune response in women [10], which is further supported by the female predominance of chronic urticaria, a condition with a pathophysiology closely linked to acquired angioedema [11].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…After reading of these 53 articles, 18 were selected for the combined analysis. 11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Seventeen articles were published in English 11,[13][14][15][16][17][19][20][21][22][23][24][25][26][27][28][29] and 1 in German. 18 The flow chart of the selection of articles is presented in Figure. None of these 18 articles 11,13-29 reported information on the prestroke mRS, alcohol consumption, weight, NIHSS at 2 and 24 hours and at 7 days, presence of infarct on imaging at 22 to 36 hours, s-ICH, infection, malignant infarct, and outcome at 3 months.…”
Section: Review Of the Literaturementioning
confidence: 99%